Pain Management Essential Topics for Examinations - Gupta, Rajesh. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Pain management is a vast subject and is changing rapidly. Finding a good resource for learning, however, is difficult. Most of the available books are lengthy volumes including many details irrelevant to physicians sitting for examinations or assessment. Furthermore, books aimed at assisting preparation for entire anaesthesia exams typically address pain management in only one chapter or a few pages.   This book covers the entire curriculum relating to pain management and will make it easy to learn all aspects of the subject by covering key concepts in a reader-friendly manner. It comprises nine concise and simple chapters that aim to impart the maximum information within a limited space. These chapters address anatomy, assessment of pain, diagnosis of pain, pharmacology, non-pharmacological pain management, acute and chronic pain management, pain management in special groups, and special techniques. Pain Management: Essential Topics for Examinations will be an ideal resource for those who plan to sit for examinations, wherever they are based in the world. In addition, it will be an invaluable reference for higher and advanced pain trainees, residents, and physicians working in chronic pain.